PENGEMBANGAN SPIRITUAL TOURISM PADA OBJEK WISATA PENGLUKATAN SIWA MELAHANGGE DI DESA SUWAT, KABUPATEN GIANYAR - Wulandari , Ni Luh Adisti Abiyoga; Febriyanti, Ni Luh Rani; Ningtias, Ni Ketut Mita; Yani, Ni Made Dwi Indra; Yani, Ni Made Devi; Rahmadhani , Vanny Dararhiska (JURNAL SEWAKA BHAKTI, 2025)
Bali is known as a popular international tourist destination for offering not only natural beauty but also unique arts and culture. Spiritual tourism is developed at Penglukatan Siwa Melahangge, which offers activities to seek inner peace through rituals and meditation or yoga. Formerly a Beji temple and a sacred place for the Suwat Traditional Village community to perform rituals, possessing a powerful magical aura, Penglukatan Siwa Melahangge has evolved into a spiritual tourism destination over time. This community service initiative aims to develop marketing strategies that support the realization of spiritual tourism for sustainable tourism development in Bali. The approach used in this activity includes mentoring in the development of marketing strategies using the 4A and SWOT methods, as well as assistance in the creation of digital marketing videos in the form of YouTube videos to support the promotion of this spiritual tourism destination.